Hypertensive disorders of pregnancy and cardiometabolic outcomes in childhood: A systematic review. (November 2019) - Jansen, Maria AC; Pluymen, Linda PM; Dalmeijer, Geertje W; Groenhof, T Katrien J; Uiterwaal, Cuno SPM; Smit, Henriëtte A; van Rossem, Lenie
Background: Hypertensive disorders of pregnancy (HDPs) are among the leading causes of maternal and perinatal morbidity and mortality worldwide and have been suggested to increase long-term cardiovascular disease risk in the offspring. Objective: The objective of this study was to investigate whether HDPs are associated with cardiometabolic markers in childhood. Search strategy: PubMed, The Cochrane Library and reference lists of included studies up to January 2019. Selection criteria: Studies comparing cardiometabolic markers in 2–18-year-old children of mothers with HDP in utero, to children of mothers without HDP. Data collection and analysis: Sixteen studies reported in 25 publications were included in this systematic review, of which three were considered as having high risk of bias. Thus 13 studies were included in the evidence synthesis: respectively two and eight reported pregnancy induced hypertension and preeclampsia, and three studies reported on both HDPs. Main results: Most studies ( n = 4/5) found a higher blood pressure in children exposed to pregnancy induced hypertension. Most studies ( n = 7/10) found no statistically significantly higher blood pressure in children exposed to preeclampsia. No association was found between exposure to HDP and levels of cholesterol, triglycerides or glucose ( n = 5/5). No studies investigated an association with (carotid) intima-media thickness, glycated haemoglobin or diabetes mellitus type 2. Conclusions: Most studies showed that exposure to pregnancy induced hypertension is associated with a higher offspring blood pressure. There is no convincing evidence for an association between exposure to preeclampsia and blood pressure in childhood. Based on current evidence, exposure to HDP is not associated with blood levels of cholesterol, triglycerides and glucose in childhood.